Pudendal nerve entrapment in an Ironman athlete: a case report - Durante, Jaclyn A. (Canadian Chiropractic Association, 2010)
OBJECTIVE: To present the diagnostic and clinical features of pudendal nerve entrapment and create awareness amongst clinicians of this rare and painful condition. CLINICAL FEATURES: A 41-year old male ironman athlete complaining of insidious constant penis pain 12–24h after long distance cycling and pain after sexual intercourse. A diagnosis of “cyclist syndrome” also known as pudendal nerve entrapment was made. INTERVENTION AND OUTCOME: Patient was treated twice a week for four weeks using the soft tissue protocol described by Active Release Technique(®) to the obturator internus muscle. After two weeks of treatment his pain decreased to a 5/10 on the pain intensity scale and he began to cycle again. After four weeks of treatment his pain had decreased to 1/10 in intensity and he continued to cycle. At follow-up, approximately 8 weeks and 12 weeks later the patient communicated that his pain is resolved and he has began to train for Ironman Lake Placid 2010. CONCLUSION: Pudendal nerve entrapment is a rare, painful condition and is often misdiagnosed due to the fact that the clinical manifestations can mimic other pathologies. It is important to be aware of the clinical features to obtain appropriate diagnosis and treatment of this condition promptly.